The Legend of Marcus Whitman and the Transformation of the American Historical Profession. Issue 1 (1st June 2018) - Koenig, Sarah
Abstract : This article explores the secularization of the American historical profession through the lens of an early twentieth-century historical controversy: the debunking of the legend that nineteenth-century missionary Marcus Whitman saved the Pacific Northwest from becoming a British possession. The Whitman controversy was a key skirmish in an ongoing, and still unresolved, debate about what constitutes right practices and ideations of history in the American academy, what counts as undue historical bias, and what place (if any) appeals to religion should have in academic historical discourse. Through the Whitman debate and other early twentieth-century historical battles, Protestant providential narratives of history were purged from academic textbooks and providential historians marginalized from the academy. Taking a cue from the evolutionary schemas of religious studies scholars, professional historians cast tales like the Whitman legend—and the providential narratives that undergirded them—as primitive myths unfit for a modernizing society. The Whitman controversy thus serves as a case study into the American historical profession's transformation at the turn of the twentieth century, a transformation that remains contested and incomplete.